O COHOUSING: BREVE ABORDAGEM JURÍDICO-PRÁTICA (De Legibus - Law Journal, 2021)
Emerging as an alternative to traditional housing, but having adapted to the needs of society in which we live, where the weakest and the elderly needgreater social protection. We are talking about collaborative housing or cohousing. Historically imbued with the principles that characterize the collaborativeeconomy, such as solidarity and support for others, the sharing of tasks and thesharing of costs, its main objective is to alleviate the difficulties of the most needy,whether economically or emotionally. Cohousing emerged to promote communitylife, where the loneliness of the senior population so characteristic of the consumer societies in which we live is fought. The object in this working paper, is a case--study of senior public-private residences, more specifically, a project that unitedthe Lisbon City Council and the Santa Casa da Misericórdia of Lisbon on behalfof social insertion.
Keywords: housing, collaborative, cohousing, residences, senior